WAYS TO IMPROVE 4C SKILLS IN FUTURE BIOLOGY TEACHERS (Web of Teachers: Inderscience Research, 2025)
This article focuses on ways to improve 4K skills in future biology teachers, such as problem solving, critical thinking, collaboration, and creativity. How to train teachers and encourage their professional development through modern pedagogical methods and innovative technologies will be considered. Strategies are developed so that teachers can apply their knowledge in practice and teach students more effectively. The article is also enriched with successful experiences and examples.